Fluorescence quenching method for monitoring oxygen diffusion into PS/CNT composite films - Yargi, O.; Ugur, S.; Pekcan, O. (ELSEVIER SCIENCE SA, 2013)
Oxygen permeabilities of nanocomposite films consisting of multi wall carbon nanotubes (MWNT) and polystyrene (PS) were determined to investigate the oxygen diffusion depending on MWNT and temperature. A method which is based on quenching of an excited phosphorescent by oxygen was applied for the measurements. The composite films were prepared from mixtures of (MWNT) and surfactant-free pyrene (P)-labeled (PS) latexes of various compositions at room temperature. These films were then annealed at 170 degrees C which is well above the glass transition (T-g) temperature of polystyrene, for 10 min. Diffusion experiments were performed for eight films with different MWNT content (0, 1.5, 3, 5, 10, 15, 25 and 40 wt%) to evaluate the effect of MWNT content on oxygen diffusion. Diffusion coefficients were found to increase from 1.1 x 10(-12) to 41 x 10(-12) cm(2) s(-1) with increasing MWNT content. On the other hand, to examine the effect of temperature on oxygen diffusion, diffusion measurements were performed over a temperature range of 24-70 degrees C for three different MWNT contents (3, 15, and 40 wt%) within the films. The results indicated that the values of the diffusion coefficient D are strongly dependent on both temperature and MWNT content in the film. It was also observed that the diffusion coefficients obey Arrhenius behavior, from which diffusion energies were determined, which increased with increase of MWNT content and temperature. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: PS; MWNT; Fluorescence; Oxygen; Quenching; LATEX FILMS; POLYSTYRENE; Chemistry; Materials Science